1992
DOI: 10.1002/jcu.1870200403
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency transvaginal sonographic examination for the potential malformation assessment of the 9‐week to 14‐week fetus

Abstract: A study was undertaken to evaluate the ability of the high-frequency transvaginal scanning method to consistently image first- and early second-trimester fetal structures, such as body contours, long bones, fingers, face, palate, feet, toes, and the four-chamber view. Ninety-seven low-risk pregnancies were scanned from 9 weeks to 14 menstrual weeks inclusive. Accurate dating was ascertained. The results showed that consistent detection of the respective structures was achieved at the following menstrual ages: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…Since the initial applications of this technique, several studies have evaluated its ability to recognize fetal organ systems in the different GA [2,6,7]. Already, transvaginal sonography makes it possible to scan and accurately scrutinize fetal anatomy, thus a knowledge of the visualization rate of the different embryonic and fetal structures at dif-ferent GA is mandatory to determine when the optimal visualization period is for embryo-fetal structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the initial applications of this technique, several studies have evaluated its ability to recognize fetal organ systems in the different GA [2,6,7]. Already, transvaginal sonography makes it possible to scan and accurately scrutinize fetal anatomy, thus a knowledge of the visualization rate of the different embryonic and fetal structures at dif-ferent GA is mandatory to determine when the optimal visualization period is for embryo-fetal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Improved image resolution and the consequential increase in the detection rate of various structures in the weeks of early pregnancy provide an increased knowledge of many aspects of normal anatomy and early embryological development [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using high-frequency transvaginal probes with twodimensional echocardiography and color Doppler flow imaging, a more detailed investigation of both hemodynamic aspects [1,2] and cardiac anatomy is feasible from 13 weeks of gestation onwards [3][4][5], and it is already possible to assess potential malformations after 11 weeks of gestation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified normal anatomic structures from 9 to 14 weeks after the last menstruation [ 1 ]. Nowadays, the early prenatal diagnosis of severe anomalies, such as neural tube defects (NTD), is possible.…”
Section: Introductionmentioning
confidence: 99%